Evaluation of 3d facial paralysis using fuzzy logic - ., Banita; Poonam Tanwar, Dr (International Journal of Engineering and Technology, 2018)
Face recognition are of great interest to researchers in terms of Image processing and Computer Graphics. In recent years, various factors become popular which clearly affect the face model. Which are ageing, universal facial expressions, and muscle movement. Similarly in terms of medical terminology the facial paralysis can be peripheral or central depending on the level of motor neuron lesion which can be below the nucleus of the nerve or supra nuclear. The various medical therapy used for facial paralysis are electroaccupunture, electrotherapy, laser acupuncture, manual acupuncture which is a traditional form of acupuncture. Imaging plays a great role in evaluation of degree of paralysis and also for faces recognition. There is a wide research in terms of facial expressions and facial recognition but limited research work is available in facial paralysis. House- Brackmann Grading system is one of the simplest and easiest method to evaluate the degree of facial paralysis. During evaluation common facial expressions are recorded and are further evaluated by considering the focal points of the left or the right side of the face. This paper presents the classification of face recognition and its respective fuzzy rules to remove uncertainty in the result after evaluation of facial paralysis.Â Â
Keywords: Stages of Face Recognition; 3D Face Recognition; CNN; Evaluation of Facial Paralysis; MAMDANI Model.